2012
DOI: 10.1177/1012690212463918
|View full text |Cite
|
Sign up to set email alerts
|

Take a deep breath: Asthma, sporting embodiment, the senses and ‘auditory work’

Abstract: ). For, whilst it is clearly of importance to address sports participation at the social-structural and ideological levels, an over-emphasis on the abstract and the macro can result in the neglect of the existential, material dimension, and the under-theorisation of the bodily aspects, the 'enfleshment' of lived sporting experience. Given the highly corporeal elements of much sports participation, such a lacuna within the sociology of sport's theoretical pantheon requires some attention. Phenomenology is, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 48 publications
0
37
0
1
Order By: Relevance
“…Our participants (and we ourselves) thus often found it difficult to describe haptic experiences. Perhaps the accounts below will evoke in the reader's body a vicarious multi-sensorial response; a form of sensory intersubjectivity (Allen-Collinson & Owton, 2012) if these accounts reverberate with her/his lived experience, despite the limitations of textual representation.…”
Section: Elemental Hapticsmentioning
confidence: 92%
See 1 more Smart Citation
“…Our participants (and we ourselves) thus often found it difficult to describe haptic experiences. Perhaps the accounts below will evoke in the reader's body a vicarious multi-sensorial response; a form of sensory intersubjectivity (Allen-Collinson & Owton, 2012) if these accounts reverberate with her/his lived experience, despite the limitations of textual representation.…”
Section: Elemental Hapticsmentioning
confidence: 92%
“…The difficulties of verbally and textually representing sensory experience have been discussed in the literature (Allen-Collinson & Owton, 2012;Sparkes & Smith, 2012) and are acutely brought home to us in re-reading, out of context, some of the quotes that follow below. There are considerable challenges in portraying in analytic textual discourse the kinds of bodily practices and experiences not usually expressed verbally or visually, the 'unrepresentable' (Merchant, 2011), or at least the 'difficult to represent'.…”
Section: Elemental Hapticsmentioning
confidence: 97%
“…This encroaches upon what might, in other theoretical traditions (such as symbolic interactionism and sociological phenomenology) be termed 'intersubjectivity' (Allen-Collinson & Owton, 2014). This lacuna in the literature may be due to Bourdieu's own approach to relationality and his relative neglect of investigation into social relationships (Bottero, 2009 King (2000) has suggested that Bourdieu does, to some extent at least, recognise the intersubjectivity of social life, but to date there has been little academic attention accorded to investigating at the micro-level the complexities of social interaction from a Bourdieusian perspective.…”
Section: Resultsmentioning
confidence: 99%
“…[looks around her]”. Such sonographic labour is a belatedly ‘under-examined’ dimension of scholarship on embodiment, let alone breath, breathing and respiratory life (Allen-Collinson and Owton 2012 ; Robinson 2019 ). In particular, such listening is a matter of being able to recognise, or not, other people with CF.…”
Section: Sonographies Of the Coughing Bodymentioning
confidence: 99%